An alternative field method for screening soybean genotypes for resistance to Heterodera glycines - Arantes, N. E.; Mauro, A. O. [UNESP]; Tihohood, D. [UNESP] (My University, 1998)
The soybean cyst nematode (Heterodera glycines) has become an increasingly severe problem in soybean production areas in Brazil. The development and use of resistant cultivars is the most efficient method of minimizing losses due to this pathogen. Our objective was to test the efficiency of an alternative method for screening soybean genotypes for resistance to H. glycines in field plots. The alternative method was compared to the standard method of sowing the test genotypes in fields found to be infested during the previous crop season. In the alternative method, the test genotypes are sown in the furrow following the uprooting of 45-day-old infected plants. The alternative method resulted in twice the cyst population and fewer escapes, and more consistent results than the standard method. The major advantage of the alternative method is that it permits screening in a more homogeneous distribution of H. glycines in the soil.
Keywords: Heterodera glycines; Resistance; Screening; Soybean; Soybean cyst nematode